A group positive psychology intervention for cancer survivors and caregivers: A pilot study of Activating Happiness©. Issue 6 (27th August 2020) - Raque-Bogdan, Trisha L.; Ash-Lee, Susan; Mitchell, Jill; Joseph, Ellen; Ross, Kaitlin; Solberg, Megan; Owen, Jesse
Abstract: The purpose of this study was to examine the feasibility and potential concept of a 4-week positive psychology group intervention (Activating Happiness©) for cancer survivors and caregivers that emphasized mindfulness, self-compassion, and gratitude. Nine facilitators led 6 intervention groups for 49 participants (35 cancer survivors, 14 caregivers). Of eligible participants, 63% enrolled and of those, 89% completed all study activities. Participants completed self-report measures at baseline, after the second and final sessions, and 3-month post-intervention, and provided qualitative feedback after the final session. Qualitative data demonstrated that participants found the intervention acceptable. The intervention's potential proof-of-concept was supported by benchmarking outcomes against those reported in randomized controlled trials, with effect sizes for mindfulness, self-compassion, anxiety, and depression for caregivers and survivors, and for pain for survivors comparable to size estimates for efficacy in clinical trials.